Themes and trends in marathon performance research: a comprehensive bibliometric analysis from 2009 to 2023 - Yan, Liping; Chen, Ziyan; Zhang, Xue; Han, Qi; Zhu, Jingyi; Wang, Qirong; Zhao, Zhiguang (Frontiers in Physiology, 2024)
When marathon runners break the 2-hour barrier at the finishing line, it attracts global attention. This study is aimed to conduct a bibliometric analysis of publications in the field of marathon running, analyze relevant research contributors, and visualize the historical trends of marathon performance research over the past 15 years. Methods On December 8, 2023, we extracted high-quality publication data from the Web of Science Core Collection spanning from January 1st, 2009 to November 30th, 2023. We conducted bibliometric analysis and research history visualization using the R language packages biblioshiny, VOSviewer, and CiteSpace. Results A total of 1057 studies were published by 3947 authors from 1566 institutions across 63 countries/regions. USA has the highest publication and citation volume, while, the University of Zurich being the most prolific research institution. Keywords analysis revealed several hotspots in marathon research over the past three years: (1) physiology of the elite marathon runners, (2) elite marathon training intensity and pacing strategies, (3) nutritional strategies for elite marathon runners, (4) age and sex differences in marathon performance, (5) recovery of inflammatory response and muscle damage. Conclusions This study presents the first comprehensive bibliometric analysis of marathon performance research over the past 15 years. It unveils the key contributors to marathon performance research, visually represents the historical developments in the field, and highlights the recent topical frontiers. The findings of this study will guide future research by identifying potential hotspots and frontiers.